Congestion in Computational Evacuation Modelling - Schneider, Volker; Könnecke, Rainer (Collective Dynamics, 2020)
The time-based analysis of egress scenarios is a long-standing and well-established method to evaluate occupant safety. It is based on the necessary condition that the required egress time is smaller than the available egress time. The former is derived by the application of evacuation models, the latter by calculation of smoke and heat spread in the case of a fire incident. In the calculation of required egress time the time-dependent development of occupant density and consequently the emergence of congestion often play a crucial role. There is a demand to evaluate the development of local occupant density and jam situations independent of the above time-based criterion. This is for example reflected in national guidelines and standards. It is however difficult to obtain general valid evaluation criteria for congestion due to the multitude of influencing parameter and the highly situation-dependent nature of the accompanying boundary conditions. In addition, prediction of localization and duration of congestion may differ from model to model if applied to equal scenarios. Furthermore, close inspection reveals the difficulty to define proper terms for a quantitative definition of congestion. This issue is further analysed in this paper based on three case studies.